Impact of debate method on Malagasy undergraduate EFL students' vocabulary mastery and their perceptions - Olivier, Gaetan; Suryati, Nunung; Karmina, Sari; Edia, Razafindralambo Miarisoa (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
Improving EFL students' English vocabulary mastery always presents an excellent challenge for both EFL teachers and students. The purposes of this study are to investigate the effectiveness of the debate method on EFL students' vocabulary improvement and explore their perceptions of the implementation for mastering vocabulary. The researchers employed a pre-experimental design integrating mixed-methods, combining quantitative and qualitative methodologies. The study involved 20 undergraduate students from the English departments at the University of Antananarivo, Madagascar, in semester 5 in the 2025 academic year. Data were collected through vocabulary tests, questionnaires, and semi-structured interviews. The results indicate a statistically significant improvement in both vocabulary knowledge size, measured by the Vocabulary Level Test (VLT) with average score rising from 29.25 to 31.60, and productive vocabulary knowledge with average score increasing from 18.50 to 21.90, measured by the Productive Vocabulary Test, both with (p<0.05). Beyond enhancing undergraduate EFL students' vocabulary, the debate method is perceived as an effective, engaging, and motivational pedagogy that promotes self-confidence. The findings suggest that the debate is an effective strategy for teaching vocabulary mastery among undergraduate EFL students and is perceived as an engaging, confidence-building pedagogical approach.